Kecerdasan Adversitas dan Kecemasan pada Ibu Nifas dalam Menghadapi Era Baru Endemi COVID-19 - Giari Rahmilasari; Intaglia Harsanti; Dessy Salamayanti Putri (Jurnal Keperawatan Silampari, 2023)
This study aims to analyze the extent of the relationship between adversity intelligence and anxiety in postpartum mothers facing the new era of the COVID-19 endemic. The research method used is a quantitative method with a cross-sectional approach. The study's results showed a negative correlation with a value of r = -0.3900, which means that the higher the adversity quotient, the lower the anxiety felt by postpartum mothers. Mothers who went through the postpartum period during the preparation for the COVID-19 endemic were in the intense anxiety range of 35%, although there were still those with the high anxiety of 11%. In conclusion, the adversity quotient is proven to affect the stress of mothers going through the postpartum period in the era of preparing for the endemic COVID-19. Keywords: Anxiety, Adversity Intelligence, Postpartum